1997
DOI: 10.1073/pnas.94.25.13701
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of fibroblast growth factor function in lens regeneration

Abstract: In urodele amphibians, lens induction during development and regeneration occurs through different pathways. During development, the lens is induced from the mutual interaction of the ectoderm and the optic vesicle, whereas after lentectomy the lens is regenerated through the transdifferentiation of the iris-pigmented epithelial cells. Given the known role of fibroblast growth factors (FGFs) during lens development, we examined whether or not the expression and the effects of exogenous FGF during urodele lens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 25 publications
0
59
0
1
Order By: Relevance
“…Fgf-2 (basic Fgf) has been shown to induce chick pigmented epithelial cells to transdifferentiate into lens fibers, suggesting a conserved mechanism (Hyuga et al, 1993). There are also studies demonstrating up-regulation of Fgf receptors in lens regeneration (Del Rio- Tsonis et al, 1997;McDevitt et al, 1997;Arresta et al, 2005). Fgf signaling is, therefore, a strong candidate for initiating transdifferentiation in competent tissues, but whether or not it is indispensible for the process has yet to be determined.…”
Section: Fgf Signalingmentioning
confidence: 99%
“…Fgf-2 (basic Fgf) has been shown to induce chick pigmented epithelial cells to transdifferentiate into lens fibers, suggesting a conserved mechanism (Hyuga et al, 1993). There are also studies demonstrating up-regulation of Fgf receptors in lens regeneration (Del Rio- Tsonis et al, 1997;McDevitt et al, 1997;Arresta et al, 2005). Fgf signaling is, therefore, a strong candidate for initiating transdifferentiation in competent tissues, but whether or not it is indispensible for the process has yet to be determined.…”
Section: Fgf Signalingmentioning
confidence: 99%
“…However, the continued expression of genes involved in embryonic lens induction in the adult newt suggests that some genes may be involved in both processes. Indeed, lens differentiation-controlling genes such as FGFs, Pax-6, Sox-2, MafB, and Prox-1 have been found in both dorsal and ventral irises of intact as well as regenerating newt eyes (10)(11)(12)(13)(14). Even though it has been established that the Pax-6 gene is expressed during the process of lens regeneration, a direct association with events of regeneration has never been established (10,13,14).…”
mentioning
confidence: 99%
“…Del RioTsonis and colleagues were the first to show the production of a second lens after FGF4 treatment in lentectomized eyes. Treatment of lentectomized newts with both FGF1 and FGF4 induced lenses with abnormal polarity due to differentiation of lens epithelial cells to lens fibers, and double lens formation from the dorsal iris [16]. These abnormalities in the regenerating lenses appeared to be similar to the lens polarity abnormalities induced during lens development in transgenic FGF mice [17].…”
Section: Fgf Signaling Pathwaymentioning
confidence: 99%
“…Several FGF receptors are expressed including FGFR1, FGFR2, and FGFR3 [16,23,24]. Detailed examination of the receptors, showed that FGFR-1 is confined to the dedifferentiating dorsal iris and plays a role in regulating lens regeneration.…”
Section: Fgf Signaling Pathwaymentioning
confidence: 99%